2001
DOI: 10.1002/ijc.1519
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of insulin-like growth factor binding protein-6 inhibits rhabdomyosarcoma growthin vivo

Abstract: Rhabdomyosarcoma is the most common soft-tissue sarcoma of childhood. Rhabdomyosarcoma cell lines overexpress insulin-like growth factor-II (IGF-II), an autocrine growth factor that is inhibited by insulin-like growth factor binding protein-6 (IGFBP-6). IGFBP-6 is associated with myoblast quiescence, and expression in rhabdomyosarcoma cells is low. The effect of IGFBP-6 on 2 rhabdomyosarcoma cell lines, RD and Rh30, was studied. IGFBP-6 inhibited anchorage-dependent growth of RD and Rh30 cells in a dosedepende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 26 publications
5
59
0
Order By: Relevance
“…They concluded that excess IGFBP-6 displaces IGF-II from IGFBP-2, thus preventing it from potentiating the mitogenic action of IGF-II (2002). Gallicchio et al (2001) also reported that IGFBP-6 dramatically inhibits xenograft growth of rhabdomyosarcoma cells.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…They concluded that excess IGFBP-6 displaces IGF-II from IGFBP-2, thus preventing it from potentiating the mitogenic action of IGF-II (2002). Gallicchio et al (2001) also reported that IGFBP-6 dramatically inhibits xenograft growth of rhabdomyosarcoma cells.…”
Section: Discussionmentioning
confidence: 94%
“…In clinical practice, DES exerted its antitumour effect on androgen-independent prostate cancer (Takezawa et al, 2001). Furthermore, IGFBP-6 inhibited the proliferation of rhabdomyosarcoma cells (Gallicchio et al, 2001). These findings prompted us to study the effect of DES and IGFBP-6 on androgen-independent prostate cancer PC-3 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intranuclear actions were also implicated in apoptosis induced by IGFBP-6 (Iosef et al 2008(Iosef et al , 2010. As described above, IGFBP-6 overexpression inhibited rhabdomyosarcoma xenograft growth and angiogenesis in vivo Gallicchio et al 2001;Zhang et al 2012), and IGFBP-6 promotes rhabdomyosarcoma cell migration via pathways dependent on PHB2 and MAP kinase signalling (Fu et al 2007.…”
Section: Rhabdomyosarcomamentioning
confidence: 98%